Modelo estrutural de avaliação dos efeitos das mudanças climáticas na estratégia das empresas do setor de energia - Freitas, Ana Rita Pinheiro de (2013)
Climate change produce consequences in all spheres of society and business, changing the way companies and governments behave and having to take steps to mitigate its effects. However some sectors of the economy turn out to be more affected than others such as the energy sector, which has strong regulation and is characterized as a strategic sector and a strong contribution to the issue of climate change. Accordingly, this project is the development and validation of a structural model to assess the effects of climate change in the energy sector, by analyzing the relationship between risk, pressure from stakeholders, response strategies and competitive advantage related to the theme. The proposed model of the analysis of the theory about the effects and challenges of climate change in the organizational context, and to evaluate the risks inherent in climate change and pressure from stakeholders impact the strategic responses of companies in the energy sector in relation to this issue, and, in turn, these responses have positive impact on the company's competitive advantage. The study is developed the Brazilian energy sector through exploratory survey applied to sector managers through web-based questionnaire. Data analysis will be through confirmatory factor analysis with the application of the technique of structural equation modeling. The results of the research point to the relationship between risks, pressure from stakeholders, the strategic responses and competitive advantage in the context of climate change on companies in the Brazilian energy sector. The results contribute to understand the behavior of energy companies face the challenges caused by climate change in order to trace the scenario of strategic responses in this sector.